2004
DOI: 10.1158/1078-0432.ccr-03-0521
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Tyrosine Kinase Inhibition by Mutant Epidermal Growth Factor Receptor Variant III Contributes to the Neoplastic Phenotype of Glioblastoma Multiforme

Abstract: Purpose:We have reported previously that tumors expressing wild-type epidermal growth factor receptor (EGFR) in a murine model are sensitive to the EGFR tyrosine kinase inhibitor gefitinib, whereas tumors expressing mutant EGFR variant III (EGFRvIII) are resistant. Determination of how this differential inhibition occurs may be important to patient selection and treatment criteria, as well as the design of future therapeutics for glioblastoma multiforme.Experimental Design: We have determined and quantified ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 35 publications
2
114
0
3
Order By: Relevance
“…However, the use of EGFR inhibitors in the treatment of glioma, while promising, remains problematic. 8,9 Published report has indicated that siRNA directed against the unique exon 1/exon 8 junction sequence of EGFRvIII can efficiently suppress its expression in human glioblastoma cell lines, leading to the reduction of the levels of phosphorylated Akt as well as the induction of partial arrest at the G2/M phase of the cell cycle. 24 Taken together, the increased expression of EGFR and the key role that this receptor may play in glioma development and progression led to the investigation of targeting EGFR for anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of EGFR inhibitors in the treatment of glioma, while promising, remains problematic. 8,9 Published report has indicated that siRNA directed against the unique exon 1/exon 8 junction sequence of EGFRvIII can efficiently suppress its expression in human glioblastoma cell lines, leading to the reduction of the levels of phosphorylated Akt as well as the induction of partial arrest at the G2/M phase of the cell cycle. 24 Taken together, the increased expression of EGFR and the key role that this receptor may play in glioma development and progression led to the investigation of targeting EGFR for anticancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…8 Another study has also demonstrated that EGFRvIII glioblastomas required higher doses, repeated dosing, and longer exposure in order to decrease its receptor phosphorylation, and such a decrease did not effectively inhibit the biologically relevant processes of DNA synthesis, cellular growth, and invasion in cells expressing EGFRvIII. 9 In a Phase II trial of gefitinib in recurrent glioblastoma, the median survival time was 39 weeks and no objective tumor responses were observed in 53 patients with recurrent glioblastoma treated with gefitinib orally. 10 Therefore, EGFR may be involved in the most important molecular event in GBMs, and it represents a valuable target for gene therapy of high-grade gliomas.…”
Section: Introductionmentioning
confidence: 99%
“…This deletion renders EGFRvIII unable to bind ligand, resulting in a receptor with weak but constitutive signaling activity, leading to enhanced tumor cell growth and survival (Rosell et al, 2006). Expression of EGFRvIII is a negative prognostic indicator in glioblastoma and mediates resistance to EGFR-targeted tyrosine kinase inhibitors (TKIs) through drug-resistant activation of Akt (Learn et al, 2004). As such, coexpression of the tumor suppressor phosphatase and tensin homologue, which opposes Akt activation, with EGFRvIII, is associated with response to EGFR-targeted TKIs both in cultured cell experiments and in a clinical setting (Mellinghoff et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has suggested that short-term treatment with gefitinib does not reduce phosphorylation of EGFRvIII and that repeated administration of gefitinib is necessary (Learn et al, 2004). Thus, to estimate the durability of gefitinib inhibition in vitro, an experiment was performed investigating the levels of EGFR/EGFRvIII and ERK phosphorylation in cells mock treated or treated with 0.1 or 2 mM of gefitinib and at the same time stimulated with 10 nM EGF for 10 min, 24, 48 and 72 h (Figure 7).…”
Section: Durability Of Gefitinib Inhibition In Vitromentioning
confidence: 99%
“…However, despite lack of ligand-binding EGFRvIII has a constitutively active receptor tyrosine kinase and is able to transform fibroblasts and to confer enhanced tumorigenicity to cancer cells both in vitro and in vivo (Huang et al, 1997;Damstrup et al, 2002;Pedersen et al, 2004). A recent study found that cells expressing EGFRvIII had increased resistance to gefitinib in vitro and in vivo, which were attributed to a deficiency in receptor dephosphorylation and constitutive AKT activity (Learn et al, 2004). Hence, evidence accumulates that signalling regulated by EGFR is altered by overexpression or mutations and that such alterations can lead to differences in response to gefitinib treatment.…”
mentioning
confidence: 99%